Adoption of Aspiration Feature in Sino-Korean Phonology - Kim, Sun-Mi (My University, 2015)
This dissertation examines the adoption of aspiration feature in Sino-Korean character readings. In broad usage, the term Sino-Korean refers to Chinese loanwords in Korean, but in this dissertation, it is used for a phonological system of Chinese-character readings (or pronunciation) derived from Middle Chinese. Although most sound correspondences between Sino-Korean and Middle Chinese are quite regular, some phonological features of Middle Chinese have been adopted irregularly into Sino-Korean, and Sino-Korean (SK) readings with aspiration discrepancy are part of this broader phenomenon of irregular SK readings. It is generally assumed that both the Chinese and Korean languages had voiceless aspirated stops and voiceless unaspirated stops at the time Chinese characters were adopted in the Korean peninsula. If that is indeed the case, a regular correspondence between Middle Chinese (MC) and SK is expected between the two languages. However, there are many cases where the aspiration feature shows irregular correspondence. Some SK readings with an unaspirated initial in their MC counterpart have an aspirated initial, while other SK readings with an aspirated initial in their MC counterpart have an unaspirated initial. Based on data from Korean annotations of Chinese texts and Korean Chinese-character rhyme books, previous researchers (Kōno, 1968; Itō, 2007) have identified analogy and syllabic inclination as two possible factors influencing the aspiration feature in SK. The analogy hypothesis is that the reading of the phonetic component of certain “frequent” characters is applied by analogy to other characters that share the same component. The syllabic inclination hypothesis is concerned with the tendency that irregular aspiration appears only in certain syllable shapes. In this dissertation, I discuss problems with the previous research and suggest an improved account of aspiration mismatch. After a thorough quantitative analysis of data, I propose hyperforeignization as an important cause for the aspiration mismatch in SK borrowings. Hyperforeignization is a process in which speakers create a form by adding a feature they perceive as foreign to a borrowed foreign word, even when that feature is not present in the original pronunciation. In my examination, I focus on what role hyperforeignization played in creating irregular SK pronunciations and its possible connections to the phenomenon of syllabic inclination. Because of the special historical context in which the written characters were main medium of borrowing in the case of SK loanwords, orthographic interference had a more significant influence compared to most other scenarios of loanword adaptation. It is probably not a single factor that is responsible for irregular SK readings, and any serious linguistic analysis must be complemented by social and cultural factors. This dissertation contributes to the field by showing how such factors may have played a role in the creation and transmission of irregular loanword readings.
Thesis (Ph.D.)--University of Washington, 2015
Keywords: aspiration feature; hyperforeignization; Sino-Korean phonology; Linguistics; Asian studies; asian languages and literature